Creating digital books with Web 2.0 tools : new opportunities for teaching and learning - Coutinho, Clara Pereira (2011)
In this paper we present tools from the Web 2.0 Internet generation, which allow to create and share books in digital format and which, in educational context, can work as an innovative strategy in the motivation for written text production and as a digital inclusion instrument. Two concrete projects are presented, regarding the use of the digital book in both the written and spoken modalities. This way, we hope to contribute to the promotion of pedagogic strategies more centered on the student and geared toward the development of reading and writing competences, as well as creativity and critical spirit, essential to all the 21st century citizens.